The influence of generator eluate in radiolabeling PSMA-11 kit with 68Ga (Brazilian Journal of Radiation Sciences, 2021)
Gaining prominence in clinical practice, the 68Ga, positron emitter radionuclide easily obtained by 68Ge/68Ga generator elution, has shown potential and excellent quality on radiolabeling of peptide for use in positron emission tomography (PET), in particular urea-based inhibitor peptides, directed to the prostate-specific membrane receptor (PSMA). Previous studies with the PSMA linked to the chelator HBED-CC (PSMA-11) radiolabeled with 68Ga showed high contrast PET/CT images to evaluate recurrence and metastasis of prostate cancer, becoming an important imaging agent in the clinical routine. This work intended to evaluate the influence of the quality of the 68Ge/68Ga generator eluate in direct labelling of PSMA-11 with 68Ga, assisting in the development of kit for prompt radiolabeling. It was evaluated the 68GaCl3 eluate from 68Ge/68Ga non-GMP generator (manufacturer A) and 68Ge/68Ga GMP generator (manufacturer B), both commercially available. To evaluate the influence of  the 68Ga eluate on radiochemical yield of the preparations,  the radiochemical purity was determined by thin layer chromatography and HPLC. The radiolabeling with non-GMP generator eluate was made with and without preliminary purification of the 68 gallium chloride eluate, employing cationic purification columns. The results showed higher radiochemical yield with the 68GaCl3 eluate from the 68Ge/68Ga GMP generator, obtaining the radiolabeled product more easily and speed to clinical practice, without preliminary purification, as opposed to the use of non-GMP 68Ge/68Ga generator which required preliminary purification of the 68GaCl3 eluate to promote satisfactory radiochemical purity results.
Keywords: prostate cancer; radiolabeling; radiopharmacy